New-onset unilateral cutaneous annular atrophic lichen planus after COVID-19 infection and reactivation after re-infections - Enas Attia (Wolters Kluwer Medknow Publications, 2023)
A huge number of related dermatological manifestations have been stated, since the outbreak of coronavirus (COVID-19) in December 2019. Here inside, a case of recent-onset unilateral cutaneous annular atrophic lichen planus (AALP) after COVID-19 infection, with reactivation after re-infection, is documented.